Effect of potential on aluminium early-stage electrodeposition onto NdFeB magnet. (4th May 2017) - Jiang, L.; Jin, Z.; Xu, F.; Yu, Y.; Wei, G.; Ge, H.; Zhang, Z.; Cao, C.
Abstract : Aluminium film has been electrodeposited onto sintered NdFeB magnet at room temperature (25°C) in ionic liquid electrolytes named aluminium chloride-1-ethyl-3-methylimidazolium chloride ionic liquid (AlCl3 -EMIC). Electrodeposition mechanism of Al film is analysed using cyclic voltammetry and chronoamperometry measurements. Structure and morphology of specimen are characterised and analysed using X-ray diffraction, energy-dispersive X-ray spectrum and atomic force microscopy. The results indicate that the process of Al electrodeposition follows the three-dimensional instantaneous nucleation mechanism. As the potentials vary from −0.4 to −0.8 V, the diffusion coefficient ( D ) of and the calculated number density of Al valid nuclei sites ( N 0 ) on the sintered NdFeB magnet both increases. The deposited films consist of pure fcc phase of Al metal, and Al grains with crystal orientation of {111}, {200}, {220} and {311} are dominant components. Al film deposited at −0.6 V has finer and smoother surface, with the roughness value of 135.10 nm.